2016
DOI: 10.1208/s12249-016-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Diminution of Particle Size and Amorphization of a Crystalline Drug Attained by Eminent Technology of Solid Dispersion: A Comparative Study

Abstract: The present study emphasized on the use of solid dispersion technology to triumph over the drawbacks associated with the highly effective antihypertensive drug telmisartan using different polymers (poloxamer 188 and locust bean gum) and methods (modified solvent evaporation and lyophilization). It is based on the comparison between selected polymers and methods for enhancing solubility through particle size reduction. The results showed different profiles for particle size, solubility, and dissolution of formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In our experiment, the crystallinity of HAP produced after aging for two days in the TEA+ET group was better, which might have been due to the fact that the Ca(OH) 2 template was a smaller and more dispersed particle. The smaller and more dispersed particles increased the specific surface area and thereby increased the surface free energy, resulting in higher solubility and dissolution [34]. At the same time, according to the description of the Ostwald-Freundlich equation, a smaller particle size not only increases the specific surface area but also increases the saturated solubility, which further improves the dissolution rate [35].…”
Section: Causes Of Structural Of Micro/nano-sized Hapmentioning
confidence: 99%
“…In our experiment, the crystallinity of HAP produced after aging for two days in the TEA+ET group was better, which might have been due to the fact that the Ca(OH) 2 template was a smaller and more dispersed particle. The smaller and more dispersed particles increased the specific surface area and thereby increased the surface free energy, resulting in higher solubility and dissolution [34]. At the same time, according to the description of the Ostwald-Freundlich equation, a smaller particle size not only increases the specific surface area but also increases the saturated solubility, which further improves the dissolution rate [35].…”
Section: Causes Of Structural Of Micro/nano-sized Hapmentioning
confidence: 99%
“…Recently, Singh et al in their study proved the effectiveness of using natural polymers for enhancing the solubility of drug as compared to synthetic polymers. The results were better analysed by determining the particle size of prepared dispersions by using particle size analyser and which were found to be in nanometric size and possessed utmost solubility upon usage of locust bean gum as a carrier [45] .…”
Section: Novel Technologies Associated With Solid Dispersionsmentioning
confidence: 99%
“…With the development of high–throughput screening technology, many new chemical drugs have been developed [1,2,3]. It has been reported that more than 40% of new active substances cannot be used clinically because of their poor water solubility, resulting in low oral bioavailability and problems with oral absorption [4,5,6,7,8]. Therefore, in order to transform more insoluble candidate compounds into new therapeutic drugs and maximize their efficacy, enhancing the solubility and bioavailability of these drugs is an important scientific problem that urgently needs to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Solid dispersion technology is a promising strategy to improve the oral bioavailability of insoluble drugs [6,7]. Inorganic porous materials including Aerosil, Syslia and Parteck have been extensively applied as drug carriers for solid dispersions [8].…”
Section: Introductionmentioning
confidence: 99%